Musical bows in south-western Angola, 1965 - Kubik, Gerhard (International Library of African Music, 1975)
Musical bows are frequently seen in south-western Angola among populations which speak Humbi, Handa and related languages. During a week's stay in the area of Quilengues and Dinde, northeast of Sa da Bandeira, in 1965, I was able to collect some data on bows and make tape recordings and 8 mm. shots of some of their varieties
Keywords: Musical bow; African Music; Angola